2008
DOI: 10.1016/j.ydbio.2008.02.028
|View full text |Cite
|
Sign up to set email alerts
|

CDC25A phosphatase controls meiosis I progression in mouse oocytes

Abstract: CDK1 is a pivotal regulator of resumption of meiosis and meiotic maturation of oocytes. CDC25A/B/C are dual-specificity phosphatases and activate cyclin-dependent kinases (CDKs). Although CDC25C is not essential for either mitotic or meiotic cell cycle regulation, CDC25B is essential for CDK1 activation during resumption of meiosis. Cdc25a -/- mice are embryonic lethal and therefore a role for CDC25A in meiosis is unknown. We report that activation of CDK1 results in a maturation-associated decrease in the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 57 publications
3
55
0
Order By: Relevance
“…In support of this idea, a cell cycle-dependent transport of Cdc25B in and out of the nucleus, has been demonstrated in somatic cells (Girard et al, 1992;Garner-Hamrick and Fisher, 1998;Dalal et al, 1999;Davezac et al, 2000) and in mouse oocytes (Solc et al, 2008). Our immunocytochemical experiments revealed a restricted cytoplasmic localization of Cdc25B in G 2 -arrested oocytes and nuclear localization shortly before GVBD.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In support of this idea, a cell cycle-dependent transport of Cdc25B in and out of the nucleus, has been demonstrated in somatic cells (Girard et al, 1992;Garner-Hamrick and Fisher, 1998;Dalal et al, 1999;Davezac et al, 2000) and in mouse oocytes (Solc et al, 2008). Our immunocytochemical experiments revealed a restricted cytoplasmic localization of Cdc25B in G 2 -arrested oocytes and nuclear localization shortly before GVBD.…”
Section: Discussionsupporting
confidence: 84%
“…The results indicated that Cdc25A also play a role in meiotic resumption of mouse oocytes. The differences in GVBD-inducing ability of the two phosphatases, Cdc25A and Cdc25B, suggest that they have different substrates and nonredundant functions (Solc et al, 2008 (Yaffe et al, 2001;Obenauer et al, 2003). This program has been quite successful and some predictions have been experimentally verified (Gratton et al, 2001;Zhou et al, 2001;Gottlieb et al, 2002;Kim et al, 2002Kim et al, , 2005She et al, 2004;Park et al, 2006;Lemeer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The subcellular localization of Chk1 was controversial, with centrosomes, nuclear, cytoplasm and kinetochores being considered as possible sites. 25,[31][32][33] We find that Chk1 is localized in the germinal vesicle and to the spindle from pro-MI to MII stages, 6 -Chk1 mRNA and arrested in M2 medium containing 2.5 μM milrinone for 2 h before being collected for western blot. (B) Change of myc was calculated by gray-scale analysis using the software Quantity one (Bio-Rad).…”
Section: Discussionmentioning
confidence: 88%
“…Oocytes were microinjected as previously described 50 in M2 medium with 5 pl of 80 ng/ml H2b-mCherry, 51 125 ng/ml Egfp-Cenp-C, 51 150 ng/ml 2mEGFP-CENP-C 23 , 50 ng/ml Securin-Egfp 52 and 125 ng/ml Map4-Egfp 53 cRNAs. Oocytes were cultured for 2 h in MEM medium supplemented with milrinone or IBMX to allow protein expression after mRNAs microinjection.…”
Section: Culture Of Oocytes and Mrna Microinjectionmentioning
confidence: 99%